BOOK REVIEWS (Journal of Finance, 1974)
Book reviewed in this article: Controlling Monetary Aggregates II: The Implementation . Money, the Financial System, and the Economy . By G eorge G. K aufman . An Introduction to Applied Macroeconomics . By E dwin K uh and R ichard L. S chmalensee Econometric Studies of Macro and Monetary Relations . Edited by A lan A. P owell and R oss A. W illiams . Financial Decision Making . By R. L. J ohnson . Finance: Environment and Decisions . By G eorge A. C hristy and P eyton F oster R oden . The Stock Market: Theories and Evidence . By J ames H. L orie and M ary T. H amilton . The Capital Market in Israel . By H aim B en ‐S hahar , S aul B ronfeld and A lexander C ukierman . The Economic Implications of an Electronic Monetary Transfer System . By M ark J. F lannery and D wight M. J affee . World Trade and Payments . By R ichard E. C aves and R onald W. J ones . The Valuation of Nationalized Property in International Law, Volume II . Edited by R ichard B. L illich . Money and Capital in Economic Development . By R onald M c K innon Financing Modern Government: The Political Economy of the Public Sector . By W illiam H. A nderson Government Finance: Economics of the Public Sector , 5th Edition. By J ohn F. D ue and A nn F. F riedlander Benefit Cost Analysis. 1971 . Edited by A. C. H arberger The Budget's New Clothes . By L eonard M erewitz and S tephen H. S osnick